The Effect of Web Design Quality and E-Trust on Repurchase Intention of Shopee Users - Budi, Wahyu Setiyoning; Isyanto, Puji; Romli, Asep Darojatul (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the effect of web design quality and e-trust on repurchase intention. The design of this study uses a quantitative method of population of shopee users at Buana Perjuangan University, with 172 students of Management study program in the period April to August 2023. Data collection through the google form questionnaire. Data processing in this study used Partial Least Square (PLS) based Structural Equation Model (SEM) analysis. The web design Quality variable has a value greater than 0.05. Both are below the significance level of 1.987. This shows that the main speculation which states that there is an impact of web design quality on repurchase intention is not proven. The e-trust variable has a p-value of 0.000 below 0.05. This shows that the second hypothesis that e-trust has an effect on repurchase is proven.